2017
DOI: 10.1111/adj.12487
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between published clinical success of direct resin composite restorations in vital posterior teeth in 1995–2005 and 2006–2016 periods

Abstract: Composites are increasing in popularity as restorative materials. This growing role indicates the necessity of studies on their clinical outcome. In this study, clinical studies published on the performance of posterior composite restorations were included except those of less than a 24-month assessment period. Results of non-vital, anterior or primary teeth and cervical single-surface restorations were also excluded. Records about composite type, number of final recall restorations, failure/survival rate, ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
1
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 67 publications
3
52
1
9
Order By: Relevance
“…The quality of matrix polymerization can impact the overall performance and longevity of the RMC restoration . A recent literature review reported an increase in RMC fracture over the past decade, where RMC failure due to fracture between 1995 and 2005 was 28.84% compared with 39.07% between 2006 and 2016 . RMC fracture may be due to multiple factors including non‐uniform polymerization across the RMC surface .…”
Section: Introductionmentioning
confidence: 99%
“…The quality of matrix polymerization can impact the overall performance and longevity of the RMC restoration . A recent literature review reported an increase in RMC fracture over the past decade, where RMC failure due to fracture between 1995 and 2005 was 28.84% compared with 39.07% between 2006 and 2016 . RMC fracture may be due to multiple factors including non‐uniform polymerization across the RMC surface .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has shown that 61% of the studied dentists had problem after performing posterior composite resin restorations. Other research has shown that only 6% of the restorations showed a primary sensitivity during 14 days [2]. In this study, in order to solve the above problems, individuals with the same skills were used and similar techniques were applied.…”
Section: Discussionmentioning
confidence: 99%
“…Today, with increased awareness, a special attention has been directed towards beauty, and as such application of tooth-colored materials, as effective factors in the beauty of smile, has increased considerably [1,2]. Various materials have been introduced regarding this spectrum including composite resin, whose application as restorer of posterior teeth has become the forefront of attention [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The composites have become the dentists' materials of choice for most restorations, due to their sophisticated aesthetic characteristics in the anterior region and due to their adequate biomechanical strength when used in posterior teeth. [2][3][4][5] Choosing an esthetic restorative material is largely due to its ability to imitate the color of the dental element. 6 Using it as a model for obtaining the optical characteristics of dentin and enamel is based on the concept of natural stratification, a simple and effective approach to manufacture highly aesthetic direct restorations.…”
Section: Introductionmentioning
confidence: 99%